Mapeamento colaborativo online como subsídio para a gestão ambiental de um campus universitário - Evangelista, Ana Nery Amaro (2017)
Environmental Management is treated as the act of thinking of spatial organization in order to plan environmental interventions that are not at all harmful to the planet, and to ensure that resources persist to future generations. The map is a powerful tool in management, because it expresses knowledge about the space where all the interactions between the various elements of nature occur. Over time, the responsibility for this planning and map control was exclusively the state. However, a new culture has been developing in the 21st century, called Participative Culture, where sharing of time and information is the primordial element. By uniting the participatory culture and the elaboration of maps we have the Collaborative Cartography. The present research aimed to understand how a collaborative cartography could help in the development of participatory environmental management of a university campus through the Open Street Map platform. The study object was the Pici Campus of the Federal University of the State of Ceará. The methodology used was subdivided into six stages: (1) preliminary cabinet work; (2) Fieldwork; (3) Mapping; (4) Semistructured interviews with campus managers; (5) Online questionnaires with users of the Pici Campus (6) Interdisciplinary proposal of Mobile Application of Participatory Management. The theoretical discussion focused on the importance of the concern with the environmental management in university campuses and the necessity of participation of the university society in the environmental management, through the construction and appropriation of the collaborative maps. Results obtained showed that the collaborative maps are used by managers and users of the campus, and have more detailed information, since they are constantly updated by the community of volunteer collaborators. It was also seen that the collaborative process of mapping a campus campus allows a greater development of spatial knowledge among campus users as well as sharpened critical awareness of the importance of environmental preservation.